Successful Outcome After Intralesional Curettage for Spindle Cell Hemangioma of Fibula in an Infant: A Case Report - Tao Han; Rufa Wang; Xiaoguang Zhou (Frontiers Media S.A., 2021)
Spindle cell hemangioma (SCH), a non-neoplastic reactive vascular lesion, rarely locates in bones. We herein report a successful case of intralesional curettage for an infant with SCH of fibula. An 11-month-old boy was admitted to our center with a painless mass in the right proximal calf. Preoperative digital radiograph demonstrated a massive vascular lesion with an irregular bone destruction of proximal fibula. The lesion was removed via the intralesional curettage approach and pathologically diagnosed as SCH. The patient gained bone structure recovery of right proximal fibula. Two years after the surgery, he experienced no local recurrence. For the management of SCH of fibula with partial bone destruction, we suggest early-stage intralesional curettage as its safety and effectiveness.